“This can certainly work…”: stakeholder perspectives of the feasibility of a caregiver-led training program for caregivers of children with cerebral palsy in a rural setting in Malawi - Bakuwa, Takondwa Connis; Saloojee, Gillian; Slemming, Wiedaad (Frontiers in Public Health, 2024)
Caregiver training is a key component of rehabilitation for children with complex lifelong disabilities such as cerebral palsy. However critical shortages of therapists in low-and middleincome countries like Malawi, reduce access to therapy. Introducing expert caregivers to assist with the provision of basic training on the condition for fellow caregivers offers a potential solution. However, there is a paucity of evidence regarding the implementation of such strategies in lowresource settings. The aim of this study was to explore perspectives of stakeholders regarding the feasibility of implementing a caregiver-led and delivered training program for caregivers of children with cerebral palsy in Malawi. Methods: Over five days in January 2023, a caregiver-led training program, the "Malamulele Onward Carer-to-Carer Training Program", was conducted in Blantyre, Malawi. A South African master trainer traveled to Malawi and delivered the program to potential , including caregivers of children with cerebral palsy; physiotherapists; and community-based organization representatives. Stakeholder perspectives regarding the acceptability, demand, practicality and adaptation of the program were obtained through a combination of focus group discussions, in-depth interviews, and daily field notes. Data from the focus group discussions and in-depth interviews were analyzed using thematic analysis. Results: The caregiver-led training program was deemed acceptable despite two areas identified as potential areas of concern; that the expert caregivers may cross practice boundaries and that their fellow caregivers may look down upon them. A demand for this program was expressed because of perceived relative advantages and relevance to caregiver needs. Participants indicated that the intervention could be easily delivered using local materials, absorbed and supported by existing community structures. Conclusion: A caregiver-led training program offers an innovative way of supporting caregivers of children with complex disabilities such as cerebral palsy in low-resource settings. The stakeholder engagement demonstrated the positive perspectives of all stakeholders. The areas for modification and adaptation highlighted by the stakeholders will be useful in strengthening the implementation of the program in Malawi.